2007
DOI: 10.1080/10635150701477825
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Choice, Rate Smoothing, and the Pattern of Tetrapod Diversification According to the Long Nuclear Gene RAG-1

Abstract: A phylogeny of tetrapods is inferred from nearly complete sequences of the nuclear RAG-1 gene sampled across 88 taxa encompassing all major clades, analyzed via parsimony and Bayesian methods. The phylogeny provides support for Lissamphibia, Theria, Lepidosauria, a turtle-archosaur clade, as well as most traditionally accepted groupings. This tree allows simultaneous molecular clock dating for all tetrapod groups using a set of well-corroborated calibrations. Relaxed clock (PLRS) methods, using the amniote = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
271
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(308 citation statements)
references
References 97 publications
(185 reference statements)
30
271
7
Order By: Relevance
“…Our rooted tree indicates that snake hepadnaviruses are probably paraphyletic and that bird hepadnaviruses (endogenous þ exogenous) are closer to mammalian than to snake hepadnaviruses, which is incongruent with the host phylogeny (in which birds are closer to snakes than to mammals [64]). This suggests that these viruses probably jumped between vertebrate hosts as well.…”
Section: Discussionmentioning
confidence: 89%
“…Our rooted tree indicates that snake hepadnaviruses are probably paraphyletic and that bird hepadnaviruses (endogenous þ exogenous) are closer to mammalian than to snake hepadnaviruses, which is incongruent with the host phylogeny (in which birds are closer to snakes than to mammals [64]). This suggests that these viruses probably jumped between vertebrate hosts as well.…”
Section: Discussionmentioning
confidence: 89%
“…Cytb has frequently been used in mammals to assess phylogenetic relationships above the family level (e.g., Agnarsson et al 2011) and has been shown to be surprisingly effective at these deeper nodes (Tobe et al 2010). As noted earlier, although saturation may introduce systemic bias in age estimates (Hugall et al 2007, Dornburg et al 2014, such bias should influence both the chipmunk and Holarctic ground squirrel clades equally as long as no calibrating fossils are incorporated a priori. At present, the best available dataset (Cytb) provides a compelling and unambiguous argument that the three chipmunk lineages exhibit genus-level genetic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic bias in molecular age estimates has been demonstrated in numerous studies (Ho and Jermiin 2004, Jansa et al 2006, Norris et al 2015. Deep branches may be underestimated relative to more recent branches (Ho and Larson 2006), especially in situations where fast-evolving genes have become saturated (Hugall et al 2007, Dornburg et al 2014). If such systemic bias is present, it may affect both chipmunks and Holarctic ground squirrels equally, but the bias would be corrected only for the Holarctic ground squirrels, thanks to the presence of a calibrating fossil.…”
Section: Introductionmentioning
confidence: 99%
“…One outgroup taxon was included (the rhynchocephalian, Sphenodon punctatus), and this species is widely recognized as the living sister group to extant Squamata (e.g. Hugall et al, 2007;Alfaro et al, 2009;Mulcahy et al, 2012). Previous studies have estimated the crown-group of living Squamata to be roughly 180-240 Myr old (review in Mulcahy et al, 2012).…”
Section: Design Of Subsampling Experimentsmentioning
confidence: 99%